RELATIONSHIP OF LEVEL OF KNOWLEDGE OF PLYWOOD FACTORY EMPLOYEES ABOUT DANGERS OF LUNG DISEASE DUE TO WORK WITH USE OF SELF PROTECTION TOOLS - Azhar, Bayu; Siti Ramalia, Siti; Elita, Veny (LPPM STIKES KENDAL, 2020)
The industrial sector becomes a job that requires a lot of  human resources, developing industries can give negative results such as air pollution by dust arising from industrial processing. This study discusses the level of knowledge of plywood factory employees about the dangers of occupational diseases with the use of personal protective equipment. This data collection uses questionnaires and collection sheets. The design of this study used a descriptive research design with the study